2016
DOI: 10.1021/acsnano.6b00241
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm for Designing Nanoscale Supramolecular Therapeutics with Increased Anticancer Efficacy

Abstract: In the chemical world, evolution is mirrored in the origin of nanoscale supramolecular structures from molecular subunits. The complexity of function acquired in a supramolecular system over a molecular subunit can be harnessed in the treatment of cancer. However, the design of supramolecular nanostructures is hindered by a limited atomistic level understanding of interactions between building blocks. Here, we report the development of a computational algorithm, which we term Volvox after the first multicellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 73 publications
0
29
0
Order By: Relevance
“…The authors also included antibodies against CD47, which is “self‐marker” often expressed on cancer cells to escape immunosurveillance. Their liposome‐like nanoparticles are distinct from traditional liposomes, as they are made from the supramolecular assembly of a novel molecular subunit that engenders weaker intermolecular interactions, enabling higher loading capabilities compared to traditional shell‐encapsulating liposomes . Finally, ISCOMATRIX is a type of lipid‐based nanocage similar to liposomes that has been used an adjuvant for prophylactic and therapeutic vaccines against infectious diseases .…”
Section: Nanoscale Materials For Immunotherapymentioning
confidence: 99%
“…The authors also included antibodies against CD47, which is “self‐marker” often expressed on cancer cells to escape immunosurveillance. Their liposome‐like nanoparticles are distinct from traditional liposomes, as they are made from the supramolecular assembly of a novel molecular subunit that engenders weaker intermolecular interactions, enabling higher loading capabilities compared to traditional shell‐encapsulating liposomes . Finally, ISCOMATRIX is a type of lipid‐based nanocage similar to liposomes that has been used an adjuvant for prophylactic and therapeutic vaccines against infectious diseases .…”
Section: Nanoscale Materials For Immunotherapymentioning
confidence: 99%
“…As the first step, we designed an amphiphilic molecular subunit that could assemble into a supramolecular structure via hydrophobic-hydrophilic interactions. In a recent study, we have described an algorithm based on quantum mechanical-all atomistic simulations to design these amphiphiles, starting from a known chemical backbone that blocked the molecular target 18,19 . The quantum mechanical energy minimized structure of an amphiphile with a CSF-1R-inhibiting pharmacophore is shown in Fig.1c.…”
Section: Computationally Simulating a Stable Supramoleculementioning
confidence: 99%
“…The quantum mechanical energy minimized structure of an amphiphile with a CSF-1R-inhibiting pharmacophore is shown in Fig.1c. Our previous studies have revealed that such amphiphiles form bilayers with co-lipids, resulting in a supramolecular structure in the nanoscale 18 . Unlike nanoparticles or liposomes, where the drug is loaded in a carrier matrix and are rarely stable beyond 5 mol% drug, the supramolecular assembly means that we could achieve excellent stability of the structures at >20 mol % of the amphiphile 18,19 .…”
Section: Computationally Simulating a Stable Supramoleculementioning
confidence: 99%
See 1 more Smart Citation
“…Getting greater insight of the non‐covalent interactions of small‐molecule drugs with peptides, proteins, or nanocarriers is essential for designing better drug transporters. Theoretical calculations have played an important role in this regard, as they have revealed molecular details of the interaction between pharmacologically active substances and their carrier or with biomolecules . Molecular dynamics (MD) computations can be utilized to optimize drug delivery agents and to study the properties of the materials, such as their structure, stability, diffusion, and interactions in biological milieu .…”
Section: Introductionmentioning
confidence: 99%